2023
DOI: 10.18632/aging.204500
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of mesenchymal stem cells on regulating Th17 and Treg differentiation in severe aplastic anemia

Abstract: Immune-mediated hematopoietic destruction is a key factor in idiopathic severe aplastic anemia (SAA). With great immunomodulatory functions, mesenchymal stem cells (MSCs) are important for bone marrow niche. While the underlying etiology of immunologic changes in SAA bone marrow remains unknown, dysfunctional MSCs are implicated as a major cause. To provide evidence for their defects in immunomodulation, alterations of SAA MSCs in regulating T cell differentiation were determined. During differentiation from C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Data from our and other labs have confirmed that BM-MSC of AA patients have cellular and molecular defects, implying a possible role of these defects being responsible for their reduced ability in sustaining HSPC functions when compared to their normal counterparts 4,[7][8][9][10][11][12] . However, the mechanism by which BM-MSC impart their functional effect on HSPC in AA remains elusive.…”
Section: Introductionsupporting
confidence: 58%
“…Data from our and other labs have confirmed that BM-MSC of AA patients have cellular and molecular defects, implying a possible role of these defects being responsible for their reduced ability in sustaining HSPC functions when compared to their normal counterparts 4,[7][8][9][10][11][12] . However, the mechanism by which BM-MSC impart their functional effect on HSPC in AA remains elusive.…”
Section: Introductionsupporting
confidence: 58%
“…The hyperinflammatory environment in severe AA is triggered by increased levels of IL-17 and IL-1β, along with decreased levels of TGF-β [16,17]. Furthermore, the single-cell profiling revealed the population of Th17-polarized CD4+CAMK4+ naïve T cells that exhibit activation of the IL-6/JAK3/STAT3 pathway, indicating a predisposition to proinflammatory pathogenesis in severe AA [18].…”
Section: Effects Of As Treatment On Enhancing Haematopoietic Function...mentioning
confidence: 99%
“…There are increasing evidences indicating that the balance between Treg cells and Th17 cells assumes a crucial role in the maintenance of immune homeostasis [ 11 ]. In patients with SAA, the immunomodulatory activity of Treg cells is impaired, whereas Th17 cells are excessively activated [ 12 , 13 ]. Thus, restoring the balance of Treg/Th17 cells can mitigate immune hyperactivity in SAA patients.…”
Section: Introductionmentioning
confidence: 99%